IMPLEMENTASI KURIKULUM MERDEKA BELAJAR GURU MATA PELAJARAN PAI DALAM PEMBENTUKAN KARAKTER SISWA - Husna, Miftahul; Ependi, Rustam (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2024)
The aim of this research is to find out to what extent the independent learning curriculum for student character development at SMP IT Khansa Khalifah Sunggal has been put into practice. This research uses qualitative methodology, meaning that the data collected is not in the form of numbers but in the form of words or photos. The aim of qualitative research is to gain a more comprehensive understanding of social phenomena by examining a broader context. This topic is closely related to the impact of this concept on character education, because this topic functions as a framework for fostering values related to character development and encouraging the cultivation of virtuous qualities. The main objective of the policy implemented in the Merdeka Belajar curriculum in schools is to ensure that students have adequate access to state-of-the-art learning facilities. The Merdeka Belajar curriculum facilitates a progressive and continuous learning process, enabling students to improve and change their character while successfully completing the given knowledge development tasks within the specified deadlines. To facilitate the implementation of learning activities actively and efficiently